Village Fund, Village Cash Transfer, and Rural Welfare: Evidence from a Sub-District Panel Analysis - Andika Isma; Sabir Sabir; Andi Naila Quin Azisah Alisyahbana (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the effects of the Village Fund and Village Cash Transfer (BLT Desa) on rural welfare. It distinguishes the Village Fund as a development-oriented fiscal instrument and BLT Desa as a protection-oriented instrument for vulnerable households. Design/methodology/approach – This study employs a quantitative explanatory approach using a balanced sub-district-year panel design for the 2021 to 2025 period. Rural welfare is measured using a composite index that reflects poverty, human development, and access to basic services. The Village Fund and BLT Desa are treated as the main explanatory variables, while disaster vulnerability is included as a control variable. The data are analyzed using a two-way Fixed Effects Model. Finding/Results – The results show that both the Village Fund and BLT Desa have positive and significant effects on rural welfare. The Village Fund has a stronger association with welfare improvement, indicating the importance of development-oriented spending in supporting infrastructure, services, and local capacity. BLT Desa also contributes positively, suggesting that direct cash assistance remains relevant for protecting vulnerable households. In contrast, disaster vulnerability has a negative and significant effect on rural welfare. Originality/Value – This study contributes to the literature by simultaneously evaluating development transfers and village-level social protection within a sub-district panel framework. The findings imply that rural welfare improvement requires an integrated village fiscal policy that combines long-term development spending, targeted household protection, and disaster-resilient planning.